Suicidal Behavior in Fibromyalgia Patients: Rates and Determinants of Suicide Ideation, Risk, Suicide, and Suicidal Attempts—A Systematic Review of the Literature and Meta-Analysis of Over 390,000 Fibromyalgia Patients - Adawi, Mohammad; Chen, Wen; Bragazzi, Nicola Luigi; Watad, Abdulla; McGonagle, Dennis; Yavne, Yarden; Kidron, Adi; Hodadov, Hadas; Amital, Daniela; Amital, Howard (Frontiers in Psychiatry, 2021)
Background: Suicide is a leading cause of death worldwide, affecting approximately 800,000 people every year. Fibromyalgia is an extremely prevalent rheumatic disease with a predisposition for comorbid anxiety and depression, which are known risk factors for suicidal behaviour. Suicidality and relevant risk factors for suicidal behaviour have not been thoroughly studied in patients with fibromyalgia. Objectives: To investigate the risk of suicidal ideation and attempts in patients with fibromyalgia. Methods: A systematic review and meta-analysis was conducted and reported according to the “Preferred Reporting Items for Systematic reviews and Meta-analyses” (PRISMA) standards. Also, the gray literature was extensively searched. Results: Thirteen studies were included in the present systematic review and meta-analysis, including 394,087 fibromyalgia patients. Sample size ranged from 44 to 199,739 subjects, mean age ranged from 45.8 to 54.5 years while female percentage ranged from 17.1% to 100.0%. The overall suicide ideation prevalence was 29.57% (95%CI 1.84-72.07), with an OR 9.12 of (95%CI 1.42-58.77), ranging from 2.34 (95%CI 1.49-3.66) to 26.89 (95%CI 5.72-126.42). Pooled suicide attempt prevalence was 5.69% [95%CI 1.26-31.34], with an OR of 3.12 [95%CI 1.37-7.12]. Suicide risk was higher with respect to the general population with an OR of 36.77 (95%CI 15.55-96.94), as well as suicide events with an HR of 1.38 (95%CI 1.17–1.71). Determinants of suicidality were found to be: employment status, disease severity, obesity and drug dependence, chronic pain and co-morbidities, in particular depression, anxiety, poor sleep, and global mental health. Conclusion: Fibromyalgia patients are particularly prone to suicide, in terms of ideation, attempt, risk and events, warranting a pre-emptive screening of their mental health status. However, in some cases, after adjusting for psychiatric conditions, the threshold of statistical significance was not achieved. Given the few studies available, the high amount of heterogeneity and the evidence of publications bias, further high-quality studies should be conducted.